Negative Impacts of Revolutions: the Cause of Wars and Crises - S. Maghdid, Rekurd; Haji Din, Badariah; Abdulrahman Hasan, Hozan; Abdulmaged Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
From the very beginning of the establishment of empires and dynasties, some people revolted against the authorities. The concept of revolutionism has become well-known when revolutionists made a series of revolutions one after another. This concept has shaped a significant impact on the political stability, economic development and mutual trust. This phenomenon has been encountered through the humanity history which varies in terms of the way of occurrence, duration, place, reason behind it and the outcomes although it has brought great changes in many aspects. Because of the effectiveness of revolutions and its impacts on all the sectors of world, some scholars have conducted studies on the reasons, outcomes and motivating ideology of the revolutionism. Thus the main purpose of this study is to discuss how the ideology of revolutionism became causes of wars, political crises, economic crises and lack of trust between powers. The paper describes revolutionism and illustrates the beginning of revolutionary waves in certain territories. Furthermore, this work explains the outcome of the recent revolutions in the Middle East especially. Ultimately, the paper ends by designing some conclusions as well as identifying areas to be taken into consideration for further research.